ISLAMIC CHARACTER EDUCATION VALUES IN MANDAILING AND ANGKOLA COMMUNITIES IN NORTH SUMATERA PROVINCE - Rahmat Hidayat; Tien Rafida (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2019)
Mandailing and Angkola culture are a culture that combines Islamic traditions and religions or is known as "Hombar do adat dohot ugamo" in their life. The existing Islamic character education values in Mandailing and Angkola communities in the North Sumatra province are constructed in such a way that the Mandailing and Angkola Communities’ character is different from other communities. This research uses a method known as ethnography or participant observation. This method is also called the naturalistic qualitative method. This method is used to examine the ongoing process of cultural systems and social systems in the communities of Mandailing and Angkola. The values that grow and develop in the Mandailing and Angkola society cultures are: (a). Religius. (b). Kinship. (c). Holong and domu (love and unity). (d). Hagabeon (descendants). (e). Hasangopan (glory). (f). Hamoraan (honor). (g). Hamajuon (progress). (h). Uhum and Ugari (law enforcement and enforcement). (i). Pangayoman (protection), and J). Marsisarian (understanding each other).Keywords: Cultural Value, Islamic character, Mandailing and Angkola